Sosialisasi dan Pelatihan Penerapan Prinsip Keselamatan dan Kesehatan Kerja (K3) pada Petani Penyadap Getah Pinus Desa Srigading Kecamatan Lawang Kabupaten Malang - Sukarno, Agus; Sulastri, Sri; Akbar, M. Taufik; Ferdian, Muh. Agus (Jurnal ABM Mengabdi, 2025)
Pine resin tapping activities carried out by the farming community in Srigading Village, Lawang District, Malang Regency, East Java have been carried out for generations, so they do not pay much attention to aspects of Occupational Safety and Health (K3). Pine resin tappers usually do not use personal protective equipment when working. If work practices like this are pursued continuously and for generations, there will be an increase in the number of deaths and accidents due to work at the pine plantation site. So it is necessary to do socialization and training. This activity aims to provide training and counseling on hazards, risks and ways to prevent occupational diseases and accidents in pine plantations. So that pine resin tappers can carry out pine resin tapping activities safely and healthily and avoid the risk of occupational diseases and accidents. This activity succeeded in increasing the level of knowledge of farmers about the dangers and risks of working in pine plantations and how to prevent them. The farmers who attended practiced directly how to use personal protective equipment, so that farmers' understanding increased. The evaluation results show that the increase in knowledge of pine tappers in the form of socialization and training on the principles of implementing Occupational Safety and Health by 51%